Efek Vinil Klorida terhadap Metilasi DNA: Tinjauan Sistematis - Nabila Azzahra Alifia; Abdul Rohim Tualeka (Media Gizi Kesmas, 2023)
Background: Vinyl chloride (VC) is a toxic chemical hazard which is characterized with colorless gas widely used in the plastics manufacturing industry. Vinyl chloride (VC) has various health threatening effects such as bothering deoxyribonucleic acid (DNA) methylation that can cause hepatocellular carcinoma (HCC) and cancer. Objectives: The purpose of writing systematic review is to determine the effect vinyl chloride (VC) to deoxyribonucleic acid (DNA) methylation. Methods: The research design is a systematic review article using PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. This question is structured by taking into account 4 stages, namely:  Population, Intervention, Comparison, and Outcome (PICO). By searching for articles/journals that match the keywords in PICO, namely "vinyl chloride (VC)” and "DNA methylation” online via Google Scholar and PubMed. Through this search, 74 articles/ journals were obtained. Then an assessment of the suitability of the inclusion criteria that has been determined in the title, abstract, and content is carried out full text so that 8 articles/ journals were obtained. Results: Based on the results systematic review, picture of cause and effect relationship vinyl chloride (VC) against deoxyribonucleic acid (DNA) methylation has been found in industrial workers who inhibit deoxyribonucleic acid (DNA) methylation which ultimately causes risk of cancer and hepatocellular carcinoma (HCC). Conclusions: There is a connection between exposure vinyl chloride (VC) and deoxyribonucleic acid (DNA) methylation that cause health hazardous effects in the form of hepatocellular carcinoma (HCC) and cancer. It's necessary to have efforts to prevent and control exposure vinyl chloride (VC), one  of which is the use of Personal Protective Equipment (PPE). Results of this systematic review are very important to be used by the government as a reference in efforts to preventing and controlling chemical exposure vinyl chloride (VC) in the work environment.